Bibliometric Analysis: Trends in Futuristic Pedagogy, Ecopedagogy, and Deep Learning in 21st-Century Education - Yusuf Tri Herlambang; Yoga Prima Putra; Iim Siti Karimah; Yusuf Tri Herlambang; Yoga Prima Putra (Jurnal Pembelajaran, Bimbingan, dan Pengelolaan Pendidikan, 2026)
Twenty-first century education faces complex challenges characterized by rapid technological advancement, globalization, and increasingly urgent environmental crises. These conditions have stimulated the emergence of innovative approaches, such as futuristic pedagogy, ecopedagogy, and deep learning, as responses to the need for more adaptive, sustainable, and meaningful learning. This study aims to analyze trends, developments, and the scientific collaboration landscape related to these three approaches using a bibliometric method. The research data were obtained from reputable scientific databases within the period 2021–2026 and analyzed using bibliometric software to identify publication patterns, dominant keywords, author collaboration networks, and the contributions of countries and institutions. The results reveal a significant increase in the number of publications addressing futuristic pedagogy, ecopedagogy, and deep learning. Furthermore, the findings indicate that developing countries are beginning to show substantial contributions to ecopedagogy studies, while developed countries remain more dominant in technology-based futuristic pedagogy. The collaboration network analysis also demonstrates a growing trend of international cooperation in the field of innovative education. This study provides a comprehensive overview of the direction of contemporary educational research and its implications for future learning practices. The findings are expected to serve as a foundation for the development of educational policies, curriculum innovation, and further research oriented toward inclusive, sustainable, and adaptive education in response to global changes.